CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF GREEN SYNTHESIS SILVER AND GOLD NANOPARTICLE FROM ZIZYPHUS AGAINST CLINICAL BACTERIA - MUKESH SHARMA; UMA BHARDWAJ; OP JANGIR (International Journal of Pharma and Bio Sciences, 2016)
Green synthesis of nanoparticles opens a new window in the biomedical research. The study was undertaken to examine, rapid and ecofriendly chemical reaction for the synthesis of Gold nanoparticles (GNP) and Silver nanoparticles (SNP) from Zizyphus nummularia (Rhamnaceae). The gold and silver nanoparticles were characterized by UV-visible spectroscopy and they gave a peak at 551 and 438 nm. Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) revealed that gold nanoparticles were observed as nanorods in shape with 208 nm in size while silver nanoparticles were spherical in shape of size 298 nm. Further, the antibacterial activity of synthesized silver and gold nanoparticles showed effective inhibitory activity against clinical isolated Escherichia coli MTCC 1302, Salmonella typhimurium MTCC 1254, Bacillus subtilis MTCC 1133 and Pseudomonas aeruginosa MTCC 2295.